Human Resource Management (Texas Journal of Multidisciplinary Studies, 2022)
Human resource management is the process of managing the human resources of an organization in tune with the vision of the top management. Human resource management function is the responsibility of all the line managers in the organization. Development of human resources is essential for any organization that would like to be dynamic and growth-oriented. Unlike other resources, human resources have rather unlimited potential capabilities. The potential can be used only by creating a climate that can continuously identify, bring to surface, nurture and use the capabilities of people.